Efficacy of Nalbuphine with Flurbiprofen on Multimodal Analgesia with Transverse Abdominis Plane Block in Elderly Patients Undergoing Open Gastrointestinal Surgery: A Randomized, Controlled, Double-Blinded Trial. (28th January 2018) - Mao, Yu; Cao, Yuanyuan; Mei, Bin; Chen, Lijian; Liu, Xuesheng; Zhang, Zhi; Gu, Erwei
Abstract : Objective . To assess different doses of nalbuphine with flurbiprofen compared to sufentanil with flurbiprofen in multimodal analgesia efficacy for elderly patients undergoing gastrointestinal surgery with a transverse abdominis plane block (TAPB). Methods . 158 elderly patients scheduling for elective open gastrointestinal surgery under general anesthesia and TAPB were randomly assigned to four groups according to different doses of nalbuphine with flurbiprofen in postoperative intravenous analgesia (PCIA). Postoperative pain intensity, effective pressing numbers of PCIA, and adverse effects were recorded at 6, 12, 24, and 48 hours after surgery. Results . Postoperative pain intensity, effective pressing numbers, and the incidence of postoperative nausea and vomiting (PONV) were similar among the four groups after surgery, while the severity of PONV was decreased in Group L compared with Group S at 6, 12, and 48 h after surgery. No individual experienced pruritus, respiratory depression, or hypotension. Conclusions . Low dose of nalbuphine (15  μ g·kg −1 ·ml −1 ) combined with flurbiprofen is superior for elderly patients undergoing elective open gastrointestinal surgery with TAPB in terms of the efficient postoperative analgesia and decreased severity of PONV. This trial is registered withNCT02984865 .